Human rights in the postgenomic era: Challenges and opportunities arising with epigenetics. (March 2020) - Dupras, Charles; Joly, Yann; Rial-Sebbag, Emmanuelle
Over the past twenty-five years, international organizations have adopted human rights declarations in an attempt to address emerging ethical, legal and social concerns associated with genetic research and technologies. While these declarations point to important challenges and potential issues in genetics, the focus on genetics has been criticized for promoting the idea that there is something unique about our genes, and that therefore, they deserve special protections in our laws. It is also argued that this 'genetic exceptionalism' perspective has contributed to a reinvigoration of genetic essentialism and determinism. In this article, we add to this criticism by pointing out gaps and flaws in current gene-focused human rights declarations in light of recent developments in the field of epigenetics. First, we show that these documents do not provide guidance for a responsible governance of epigenetic data (e.g., privacy protection) and an ethical use of individual epigenetic information (e.g., nondiscrimination). This is particularly concerning given the interest recently demonstrated by insurance companies, forensic scientists and immigration agencies in using epigenetic clock technologies. Second, we argue that findings in epigenetics could contribute to the promotion of second- and third- generation human rights, i.e., respectively, economic, social and cultural rights, and solidarity rights. We conclude by calling for international bioethics and human rights organizations to pay greater attention to epigenetics and other postgenomic sciences in the coming years.